A Helpful Clue to Calciphylaxis: Subcutaneous Pseudoxanthoma Elasticum–like Changes. (July 2020) - Chen, Eric L.; Altman, Igor; Braniecki, Marylee
Abstract : Abstract: Calciphylaxis, otherwise known as calcific uremic arteriolopathy, is an aggressive disease characterized by painful, ischemic skin lesions with histologic findings of microvascular calcification involving the fat. It is most commonly seen in patients with end-stage renal disease who are on dialysis. Early diagnosis is pivotal for optimal management. However, calciphylaxis can be challenging to diagnose, as many diseases can bear a clinical resemblance to calciphylaxis. Skin biopsies are often necessitated for diagnosis, but unfortunately, one is commonly challenged with a suboptimal amount of subcutaneous fat that does not always show the classic findings of microvascular calcification. However, when calciphylaxis is clinically suspected, the microscopic detection of subcutaneous pseudoxanthoma elasticum (PXE)-like changes, although not unequivocally diagnostic of calciphylaxis, can be a helpful clue in the diagnosis. We report a case of a 49-year-old woman who was diagnosed with uremic calciphylaxis on the basis of the clinical scenario, laboratory testing, and microscopic presence of subcutaneous PXE-like changes that was highlighted with the elastic and von Kossa stains. This case demonstrates the importance of recognizing subcutaneous PXE-like changes on suboptimal skin biopsies that lack microvascular calcification, especially in those patients who are clinically suspect for calciphylaxis as to prevent delay in diagnosis and treatment.